Nanoformulated Bumetanide Ameliorates Social Deficiency in BTBR Mice Model of Autism Spectrum Disorder - Lv, Hui; Gu, Xiao; Shan, Xingyue; Zhu, Tailin; Ma, Bingke; Zhang, Hao-Tian; Bambini-Junior, Victorio; Zhang, Tiantian; Li, Wei-Guang; Gao, Xiaoling; Li, Fei (Frontiers in Immunology, 2022)
Autism spectrum disorder (ASD) is a prevalent neurodevelopmental disorder with few medication options. Bumetanide, an FDA-approved drug, has been proposed as a viable candidate to treat core symptoms of ASD, however neither the brain region related to its effect nor the cell-specific mechanism(s) are unclear. The availability of nanoparticles provides a viable way to identify pharmacological mechanisms for use in ASD. Here we found that treatment with bumetanide, in a systemic and medial prefrontal cortex (mPFC) region-specific way, attenuated social deficits in BTBR mice. Furthermore, using poly (ethylene glycol)-poly(l-lactide) (PEG-PLA) nanoparticles [NP(bumetanide)], we showed that the administration of NP(bumetanide) in a mPFC region-specific way also alleviated the social deficits of BTBR mice. Mechanistically, the behavioral effect of NP(bumetanide) was dependent on selective microglia-specific targeting in the mPFC. Pharmacological depletion of microglia significantly reduced the effect of nanoencapsulation and depletion of microglia alone did not improve the social deficits in BTBR mice. These findings suggest the potential therapeutic capabilities of nanotechnology for ASD, as well as the relevant link between bumetanide and immune cells